Paving the Way for Out-of-School Youth by Strengthening Digital Content Creation Skills - Monika Teguh; Imanuel Deny Krisna Aji; Kuncoro Dewi Rahmawati; Ignasius Liliek Senaharjanta; Cosmas Gatot Haryono (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Education is the right of every citizen. Unfortunately, various social and economic problems cause unfortunate youths to drop out of school. Without the provision of education, these young people are threatened with difficulties in getting a job and a decent life in the future. In response to this problem, a French NGO called Life Project For Youth (LP4Y) provides assistance by providing certified informal education and training for out-of-school youth in various regions of the world, one of which is in Indonesia, in the city of Surabaya. In carrying out its mission LP4Y realizes that they do not always have experts to teach the knowledge or skills needed by the youth, so they collaborate with Ciputra University Surabaya as a partner in developing fostered youth. Specifically in this activity, the purpose of the service carried out is to strengthen the skills of young people in the field of content creation, and encourage their confidence to use these skills. The methods used include training, technology application, and mentoring. Then evaluated through surveys to participants and implementing partners. Participants who took part in the activity consisted of 15 young people. From this activity, participants have succeeded in making photo and video works that become portfolios for them to find jobs in fields that require these skills. Participants also stated that they are more confident to seek employment in fields other than administration due to the new skills they learned. Pendidikan merupakan hak setiap warga negara. Namun sayangnya berbagai permasalahan sosial dan ekonomi menyebabkan pemuda-pemuda yang tidak beruntung harus mengalami putus sekolah. Tanpa adanya bekal pendidikan, maka pemuda ini terancam akan kesulitan mendapatkan pekerjaan dan hidup yang layak ke depannya. Menanggapi permasalahan ini, sebuah LSM dari Perancis bernama Life Project For Youth (LP4Y) memberikan bantuan dengan memberikan pendidikan dan pelatihan informal bersertifikat bagi para pemuda putus sekolah di berbagai wilayah di dunia, salah satunya adalah di Indonesia, di kota Surabaya. LP4Y menyadari bahwa mereka tidak selalu memiliki tenaga ahli untuk mengajarkan ilmu atau skill yang dibutuhkan oleh para pemuda, sehingga mereka menggandeng Universitas Ciputra Surabaya sebagai mitra dalam mengembangkan para pemuda binaan. Secara khusus dalam kegiatan ini, tujuan pengabdian yang dilaksanakan adalah untuk memperkuat skill para pemuda di bidang content creating, serta mendorong kepercayaan diri mereka untuk menggunakan skill tersebut. Metode yang digunakan antara lain pelatihan, penerapan teknologi, dan pendampingan. Kemudian di evaluasi melalui survei kepada peserta maupun mitra pelaksana. Peserta yang mengikuti kegiatan terdiri dari 15 orang pemuda. Dari kegiatan ini, peserta telah berhasil membuat karya foto dan video yang menjadi portofolio bagi mereka untuk mencari pekerjaan di bidang yang membutuhkan skill tersebut. Peserta juga menyatakan mereka lebih percaya diri untuk mencari pekerjaan di bidang lain selain bidang administratif berkat skill bari yang mereka pelajari. Implikasi dari kegiatan pengabdian kepada masyarakat ini adalah para pemuda putus sekolah yang memiliki keterampilan baru di bidang digital content creating.